THE EFFECT OF PRODUCT QUALITY, PRICE, AND PROMOTION ON CONSUMER SATISFACTION OF “CHARLES & KEITH” BAGS (Study on Consumers in Denpasar City) - Febronia Julia; Ni Nyoman Kerti Yasa (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The fashion industry is one of the most dynamic global economic sectors and continues to change over time. Fashion products now not only function as basic necessities and part of a lifestyle, but also have a strong influence on society. One of the fashion items that is highly sought after by women in the current era of fashion development is bags. Charles & Keith is a fashion brand widely known for its bag products. This study aims to determine the effect of product quality, price, and promotion on consumer satisfaction of Charles & Keith bags in Denpasar City. The method used to determine the sample in this study was purposive sampling with a sample size of 120 respondents. The data collection method in this study was through the distribution of research instruments in the form of offline distribution by giving directly to respondents and online via Google Form with the help of social media to consumers of Charles & Keith bag products in Denpasar City. The data analysis technique used was regression analysis with the help of SPSS for Windows. The results of the study showed that product quality, price, and promotion have a positive and significant effect on consumer satisfaction. Based on the results of this study, it is expected that Charles & Keith will improve various aspects related to product quality, price, and promotion to increase consumer satisfaction.